Identification of Hub Genes Associated With Melanoma Development by Comprehensive Bioinformatics Analysis - Jiang, Jie; Liu, Chong; Xu, Guoyong; Liang, Tuo; Yu, Chaojie; Liao, Shian; Zhang, Zide; Lu, Zhaojun; Wang, Zequn; Chen, Jiarui; Chen, Tianyou; Li, Hao; et al. (Frontiers in Oncology, 2021)
Introduction This study aimed to identify important genes associated with melanoma to further develop new target gene therapies and analyze their significance concerning prognosis. Materials and methods Gene expression data for melanoma and normal tissue were downloaded from three databases. Differentially co-expressed genes were identified by WGCNA and DEGs analysis. These genes were subjected to GO, and KEGG enrichment analysis and construction of the PPI visualized with Cytoscape and screened for the top 10 Hub genes using CytoHubba. We validated the Hub gene’s protein levels with an immunohistochemical assay to confirm the accuracy of our analysis. Results A total of 435 differentially co-expressed genes were obtained. Survival curves showed that high expression of FOXM1,\ EXO1, KIF20A, TPX2, and CDC20 in melanoma patients with 5 of the top 10 hub genes was associated with reduced overall survival (OS). Immunohistochemistry showed that all five genes were expressed at higher protein levels in melanoma than in paracancerous tissues. Conclusion FOXM1, EXO1, KIF20A, TPX2, and CDC20 are prognosis-associated core genes of melanoma, and their high expression correlates with the low prognosis of melanoma patients and can be used as biomarkers for melanoma diagnosis, treatment, and prognosis prediction.